Performance of nickel catalyst toward photocatalytic degradation of methyl orange - Muhammad Farhan, Hanafi; Norzahir, Sapawe (Elsevier Ltd., 2020)
In this study, the EGNiO1000 that generated using new green electrolyte Nephelium lappaceum extract via electrochemical system shows excellent photoactivity toward MO degradation up to 96.8 under visible light irradiation compared to EGNiO0, EGNiO50, commercial NiO, and commercial TiO2 catalyst. The presence of bioactive compound such as polyphenols, alkaloids, flavanoids and vitamins. The active component that presence in Nephelium lappaceum such as polyphenols, alkaloids, flavanoids and vitamins, are highly responsible for improving the structural, morphological and optical properties of EGNiO1000, thus lead to the enhancement on the photodegradation activity. Green approach with simple electrochemical system display a great potential to generate of other novel metal catalyst with excellent photoreaction.